2002
DOI: 10.1590/s1413-86702002000100004
|View full text |Cite
|
Sign up to set email alerts
|

Childhood pneumonia: clinical aspects associated with hospitalization or death

Abstract: Several clinical aspects may be used in assessing need for hospitalization (i.e. young age, malnutrition, underlying chronic illness, tachypnea, chest indrawing and somnolence) for children with pneumonia seen at the ER. Individual intrinsic factors such as age, malnutrition and underlying chronic illness were independently associated with death. Pneumonia should be considered a treatable disease and complete recovery can be achieved in the majority of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
5
16
0
6
Order By: Relevance
“…Case death rate (0.8%) was based on data from the National Mortality Information System (Sistema de Informação sobre Mortalidade, SIM) 22. Similar rates were found in the literature 17 20. It was assumed that no death occurred in children with pneumonia treated at outpatient healthcare facilities.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…Case death rate (0.8%) was based on data from the National Mortality Information System (Sistema de Informação sobre Mortalidade, SIM) 22. Similar rates were found in the literature 17 20. It was assumed that no death occurred in children with pneumonia treated at outpatient healthcare facilities.…”
Section: Methodssupporting
confidence: 92%
“…Since Brazilian data for the number of pneumonia cases treated in outpatient healthcare facilities were absent, estimates were based on the number of hospitalisations due to pneumonia and the proportion of children <5 seen in emergency rooms who were hospitalised. Data from the Brazilian literature indicated that 40–44% of the infants and 18–28% of children aged 1–4 years with pneumonia diagnosed at the public emergency rooms are hospitalised 17 18. A household survey showed a higher proportion of hospitalisation at the private healthcare system 19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os aspectos nutricionais e as comorbidades também foram relatados enquanto fatores envolvidos na hospitalização por pneumonia, em um estudo transversal desenvolvido na Bahia, Brasil (NASCIMENTO-CARVALHO et al, 2002), que identificou uma chance 2 vezes maior de internação entre crianças mal nutridas (OR=2,0) e um risco 40% maior de internação entre as portadoras de doenças crônicas (OR=1,4), incluindo cardiopatia, neuropatia, asma, refluxo gastroesofágico, infecção congênita e hipotireoidismo.…”
Section: Ira Em Crianças Menores De Cinco Anos De Idade Aunclassified
“…Os benefícios do aleitamento materno para as crianças têm sido relacionados às menores taxas de diarreia, infecções do trato respiratório, otite média e outras infecções, e menor mortalidade por essas doenças em crianças amamentadas quando comparadas às não amamentadas (LEÓN-CAVA et al, 2002 Por fim, sem a pretensão de esgotar as possibilidades de atenção à criança na APS, destaca-se a importância do acompanhamento, controle e manejo de condições crônicas capazes de predispor a criança a um quadro grave de pneumonia, como as doenças de base pulmonar, as doenças cardiovasculares, as neuropatias graves, as doenças metabólicas e as imunológicas (JACKSON et al, 2013;NASCIMENTO-CARVALHO et al, 2002;RAMACHANDRAN, et al, 2012;SIGAÚQUE et al, 2009).…”
Section: Identificou Que Ounclassified